Blends in Media and Advertising Discourse in Contemporary Croatian Language - Štebih Golub, Barbara (Poznańskie Studia Slawistyczne, 2017)
The paper deals with blends – compound words which are formed by blending of form and meaning of two (or more) words – in contemporary Croatian language. Due to their structural peculiarity and expressiveness, they have been very frequent in Croatian language of commercials and media during the last decade or so. On the basis of corpus collected from Croatian commercials, electronic publications and news portals from 2009 to 2016, the paper analyses the structure of blends, their meanings and their place in the lexical system of Croatian language.